The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.11591/ijeecs.v19.i3.pp1626-1634
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effect of electronic nose sampling for classifying mixture of beef and pork

Abstract: Strong demand and strong price of raw foodstuffs like beef was commonly used in conventional markets by beef dealers to commit fraud in order to gain larger income. The fraud has been in the form of combining beef and pork. In Indonesia, this has been a issue of food health in recent years. Via scent, some food safety concerns can be expected. By using electronic nose that is equipped with electrochemical and air sensors  such as temperature sensors, strain, and humidity to find the pure beef or mixed beef. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…To prevent products' adulteration, Świgło and Chmielewski [5] proposed an e-nose to assist in the authenticity testing of products such as meat, honey, milk, and plant oils. To discourage meat dealers from committing food fraud, Laga and Sarno [6] presented an e-nose discriminating pork from beef. Wang et al [7] deployed an e-nose inside a domestic refrigerator to assess the food freshness level of fruits, vegetables, and meat.…”
Section: Introductionmentioning
confidence: 99%
“…To prevent products' adulteration, Świgło and Chmielewski [5] proposed an e-nose to assist in the authenticity testing of products such as meat, honey, milk, and plant oils. To discourage meat dealers from committing food fraud, Laga and Sarno [6] presented an e-nose discriminating pork from beef. Wang et al [7] deployed an e-nose inside a domestic refrigerator to assess the food freshness level of fruits, vegetables, and meat.…”
Section: Introductionmentioning
confidence: 99%
“…Since aroma still becomes the main parameter in food products quality control, the use of aroma meters such as an e-nose will increase in the future, including in the determination of fish products quality. Currently e-nose is widely used in various fields such as quality control of food products [9][10], assessment and classification of meat freshness [11]- [13], determination of fish freshness [8], classification of fruits [14], characterization of tea aroma [15]- [16], identification and classification of coffee aroma [17]- [25], identification of environmental quality [26], and medical purposes such as identification of respiratory disease [27]. E-nose produces a specific response when a sample of aroma compound is exposed on the sensor array headspace.…”
Section: Introductionmentioning
confidence: 99%
“…This algorithm can be used for simple classification with fixed Y variable and also for text classification [14]- [16]. Laga and Sarno [17] showed that Naïve Bayes gave the best accuracy from other classification methods, such as KNN, SVM, and random forest. However, the Naïve Bayes algorithm still has a drawback, that is, if the probability value from one of the variables is 0, it can make the final comparison result 0, which can lead to inaccurate prediction results [15], [17]- [20].…”
Section: Introductionmentioning
confidence: 99%
“…Laga and Sarno [17] showed that Naïve Bayes gave the best accuracy from other classification methods, such as KNN, SVM, and random forest. However, the Naïve Bayes algorithm still has a drawback, that is, if the probability value from one of the variables is 0, it can make the final comparison result 0, which can lead to inaccurate prediction results [15], [17]- [20]. Research [15], [17] overcomes zero probability with RB-Bayes, while research [20] uses Hybrid N-gram, and research [19], [20] uses multinomial Naïve Bayes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation